Application and algorithm research of TDLAS. Issue 1 (1st October 2022) - Wei, Lao; Hu, Cui; Xuanjun, Wang; Zhongkai, Qu
Abstract : Tunable diode laser absorption spectroscopy (TDLAS) is extensively utilized in monitoring of trace gases in the environment. With the relative entropy tomographic reconstruction, simultaneous multiplicative algebraic reconstruction technique algorithm and optimization of existing functions and models, TDLAS has been applied to reconstruction of temperature and humidity field, combustion diagnosis, mass flow monitoring and other domains, this paper will analyze the existing TDLAS application and algorithm research.